EKSPLORASI CENDAWAN ENDOFIT DARI TANAMAN CABAI YANG BERPOTENSI SEBAGAI AGENS BIOKONTROL PENYAKIT ANTRAKNOSA (Colletotrichum acutatum L.) (Exploration of Endophytic Fungi from Pepper as Biological Control Agents of Anthracnose (Colletotrichum acutatum L.) - Weni Wilia; . Widodo; Suryo Wiyono (Bioplantae, 2013)
Anthracnose caused by Colletotrichum acutatum is one of devastated disease of pepper in Indonesia and has great impact on yield loss. Most of farmers use fungicides as controller for this disease. Application of biocontrol agents could be solution to control anthracnose. Beneficial microorganism, such as endophytic fungi are able to be promising biocontrol agents of some pathogens, including Colletotrichum acutatum. The aim of this research was to isolate endophytic fungi from fruit and branch as biocontrol agents for pepper anthracnose. The research resulted 11 isolates of endophytic fungi that were further tested against anthracnose. Isolates of endophytic fungi were identified as steril hifa hitam 1, steril hifa hitam 2, steril hifa 1, steril hifa 2, Nigrospora sp., Coniotyrium sp., Cylindrocarpon sp., Paecilomyces sp. The 3 of other isolates (isolat buah 5, isolat buah 1dan isolat batang 24) were not identified yet.   Keyword : Pepper, antrachnose, C. acutatum, endophytic fungi